Company training and services : focus on low skills - Asplund, Rita; Salverda, Wiemer (International journal of manpower ;, 2004)
This special issue of the International Journal of Manpower aims to make a contribution to broadening our limited understanding of the role and impact of employer-provided training for low-skilled service sector workers. It brings together seven of the papers that were presented at the international conference "Adapting Education and Training for the Enhancement of Low-Skilled Jobs" held at Helsinki in May 2002. The papers are situated at the crossroads where three different strands of research and policymaking meet: the training of the low skilled, the system of vocational training and the ro